Security on Cloud Resource Consumption of Malicious Attacks – A Systematic Review - Shaheen, H; Kumar, S. Vinoth; Vidhya, S; Ravikumar, K; Girirajan, S; Senthilkumar, R (Journal of Telecommunications and the Digital Economy, 2026)
An ever-increasing number of buyers are moving to the public cloud and facilitating their applications on cloud cost-effectively to benefit from enhanced high accessibility and versatility. Malicious Cloud Bandwidth Consumption (MCBC) is one type of threat where attackers consume the cloud bandwidth slowly and continuously for an extended time, causing a financial burden to the cloud consumer. This research emphasises securing cloud web resource consumption by detailing MCBC attacks and proposes a methodology for building classifiers using Machine Learning (ML) to detect malicious requests accurately. Then, at that point, we evaluate the performance of each method based on its features, advantages, and limitations. Additionally, we also outline future research directions for developing improved cloud computing models.